The Effectiveness of Cinematherapy Techniques for Reducing Body Dissatisfaction in Early Adult Women - Atikah, Ummul; ., Widyastuti; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Ideal beauty standards in society can cause early adult women to experience body dissatisfaction, so efforts are needed in the form of cinematherapy intervention. This study aims to determine the effectiveness of cinematherapy techniques to reduce body dissatisfaction in early adult women. The subjects in this research were 6 students from the Faculty of Economics aged 18-25 years. This research uses a pre-experimental research design, one group pretest-posttest design. This research uses the Wilcoxon test with the results of data analysis which obtained a significance level value of p = 0.0135 (p < 0.05), meaning that H0 is rejected and Ha is accepted. The results of this study indicate that cinematherapy techniques are effective in reducing body dissatisfaction in early adult women. So it can be concluded that cinematherapy techniques can be used to reduce body dissatisfaction in early adult women